Preface - Human, Suzanne (Acta Academica: Critical views on society, culture and politics, 2012)
From text: This volume of articles originated as a result of an initiative during 2010 and 2011 among researchers in the cultural disciplines in the Faculty of the Humanities at the University of the Free State to form an interdisciplinary research group which discussed readings of mutual interest. The broad topic of these seminars was the Translatability of Cultures. As teachers of culture at a tertiary institution in South Africa we are constantly confronted with questions about the modes in which cultural translations continuously take place between “Africa” and “the West”, some-times unnoticed and sometimes in a premeditated way. A number of research articles grew in this context and related articles were solicited from colleagues in Africa, Europe and America to form this collection.